(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The children’s development after the family, the educational institutions will be determined. The maturational program and the environmental effects affect the personality development. In the kindergarten, the observations, experiences and emotions are very important for children development. Components of the emotional relations to the kindergarten are significant: /1/ the relation with the kindergarten teacher, /2/ the relation with the children, /3/ the connection with the activities, events, celebrations /4/ and the connection with the physical environment. This study a research result describe about the children’s connections with their kindergarten.